Killing in 'the good old Irish fashion'? Irish revolutionary violence in context. Issue 165 (May 2020) - Dolan, Anne
Abstract: In comparison to many parts of post-war Europe, Ireland's wars between 1919 and 1923 were not as lethal as they might have been. This article addresses some of the possible reasons why, reasons that were quite specific to the immediate Anglo-Irish context but reasons that may also have been due to broader transnational understandings of what it was to be a soldier, what it was to fight at that time. But while comparative fatality rates may leave Ireland somewhat overshadowed, this article considers what Ireland's wars still share with other conflicts and looks at some of the dimensions of Irish violence that were, irrespective of numbers killed, still fundamentally the same as violence experienced in other periods and places. Tackling some of the challenges of contemporary comparisons, the article suggests other possible comparisons ranging far beyond the inter-war period that may prove more fruitful, and asks whether the nature of violence shapes our perceptions of a conflict far more than fatality rates do.